UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL INKUIRI PADA MATA PELAJARAN IPAS KELAS VI SD NEGERI 064974 MEDAN TAHUN PEMBELAJARAN 2024/2025 - Ruslan Pasaribu; Muhammad Arifin; Tetty Rosmaida Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve student learning outcomes through the application of the class VI Inkuri learning model at SD Negeri 064974 Medan Tembung for the 2024/2025 academic year. The subjects in the research were 20 class VI students. The techniques used by researchers in collecting data are observation and tests. The learning model used in this research is the Inquiry learning model. This research shows an increase in student learning outcomes in the science and science subject DEVELOPMENT OF LIVING CREATURES in class VI of SD Negeri 064974 Medan Tembung for the 2024/2025 academic year. This is evident from the results of research conducted on the pretest (initial test) which received a complete score of 6 students or 25%, while those who received an incomplete score were 15 students or 75%, with an average learning result of 56.7. The results of the research in the first cycle increased to 8 students who were completed or 40%, while 12 students who did not complete it or 60% with an average score of 65. In the second cycle, the completeness of students' learning outcomes increased to 17 people or 85% of students who completed it while those who did not. 3 students or 15% have completed it with an average score of 87, then there has been an increase in cycle I to cycle II and they have fulfilled the specified completion. Furthermore, from the results of observations of teacher activities in carrying out learning in cycle I, an average of 72% (Good) was obtained and in cycle II it increased to 92% (Very Good) and the results of observations of student activities in cycle I obtained an average score of 62%. (Good) and increased in the second cycle to 92% (Very Good). Thus, it was concluded that by using the inquiry learning model there was an increase in student learning outcomes in the science and science subject in class VI of SD Negeri 064974 Medan Tembung for the 2024/2025 academic year.